Automatic facial coding predicts self-report of emotion, advertisement and brand effects elicited by video commercials - Höfling, T. Tim A.; Alpers, Georg W. (Frontiers in Neuroscience, 2023)
Introduction Consumers’ emotional responses are the prime target for marketing commercials. Facial expressions provide information about a person’s emotional state and technological advances have enabled machines to automatically decode them. Method With automatic facial coding we investigated the relationships between facial movements (i.e., action unit activity) and self-report of commercials advertisement emotion, advertisement and brand effects. Therefore, we recorded and analyzed the facial responses of 219 participants while they watched a broad array of video commercials. Results Facial expressions significantly predicted self-report of emotion as well as advertisement and brand effects. Interestingly, facial expressions had incremental value beyond self-report of emotion in the prediction of advertisement and brand effects. Hence, automatic facial coding appears to be useful as a non-verbal quantification of advertisement effects beyond self-report. Discussion This is the first study to measure a broad spectrum of automatically scored facial responses to video commercials. Automatic facial coding is a promising non-invasive and non-verbal method to measure emotional responses in marketing.